The Effect of Extract Ciplukan (Physalis angulata L.) to Placental Vessels, Placental Weight and Fetal Birth Weight in Preeclampsia Rat Model - Nur Permatasari (Journal of Global Pharma Technology, 2020)
Background: Preeclampsia, which is one of the specific diseases of pregnancy at the age of 20 weeks. Preeclampsia is due to the vascular abnormalities of placenta that can cause chronic hypoxia of the placenta and the fetus's nutritional disorder, causing impaired function of the placenta, and fetal development during pregnancy. Physalis angulata L. contains antioxidants, and anti-inflammatory effects in improving placental function and preventing nutritional disorders in the fetus. The study aims to determine the effect of Physalis angulata L. against the number of placental blood vessels (capillaries), the weight of placenta and birth weight fetus on the preeclampsia rat model. Methods: The research is an experimental laboratory study conducted in vivo design consisting of five groups; Negative control group, positive control group (preeclampsia rat model), preeclampsia rat treatment group with therapeutic dose 1, dose 2, and dose 3 (500mg/kg/BB; 1500mg/kg/BB; 2500mg/kg/BB). Counting the number of capillaries with the H&E stain method, the placenta weight and the fetus weight is measured immediately using analytical balances. Data analysis using One-way Annova test. Result: The results showed significant difference of capillaries p value < 0.05 (p = 0,000), the placenta weight p value < 0.05 (0.025), and the birth fetal weight p value < 0.05 (0.002). Conclusion: Physalis angulata L. can be a potential antioxidant in preeclampsia through increased eNOS and NO level which can improve the function of the placenta in preeclampsia rats so that the number of placenta capillaries increased, while the placenta weight and the fetal weight increased. Keyword: Preeclampsia, Placenta Vessels (capillaries), Placenta Weight, Fetal Weight, eNOS, NO